2022
DOI: 10.4049/jimmunol.2100784
|View full text |Cite
|
Sign up to set email alerts
|

Innate and Adaptive Immunity to Transfused Allogeneic RBCs in Mice Requires MyD88

Abstract: RBC transfusion therapy is essential for the treatment of anemia. A serious complication of transfusion is the development of non-ABO alloantibodies to polymorphic RBC Ags; yet, mechanisms of alloantibody formation remain unclear. Storage of mouse RBCs before transfusion increases RBC immunogenicity through an unknown mechanism. We previously reported that sterile, stored mouse RBCs activate splenic dendritic cells (DCs), which are required for alloimmunization. Here we transfused mice with allogeneic RBCs to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…Prior studies have demonstrated that the role of complement, innate immune signaling events and even the relative requirement of CD4 T cells can fundamentally differ between distinct RBC alloantigens. 18,[24][25][26] These outcomes appear to be driven in part by the unique antigens themselves 18,[24][25][26] ; this is further evident by the present results, as the impact of RBC storage on alloimmunization outcomes was largely preserved even when HOD and KEL were present on the same RBC. As with any approach, this study is not without limitations.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Prior studies have demonstrated that the role of complement, innate immune signaling events and even the relative requirement of CD4 T cells can fundamentally differ between distinct RBC alloantigens. 18,[24][25][26] These outcomes appear to be driven in part by the unique antigens themselves 18,[24][25][26] ; this is further evident by the present results, as the impact of RBC storage on alloimmunization outcomes was largely preserved even when HOD and KEL were present on the same RBC. As with any approach, this study is not without limitations.…”
Section: Resultssupporting
confidence: 64%
“…The ability of storage to differentially impact RBC‐induced alloimmunization in an antigen‐specific manner adds to growing evidence that distinct RBC antigens may engage unique immune pathways when inducing alloantibody formation. Prior studies have demonstrated that the role of complement, innate immune signaling events and even the relative requirement of CD4 T cells can fundamentally differ between distinct RBC alloantigens 18,24–26 . These outcomes appear to be driven in part by the unique antigens themselves 18,24–26 ; this is further evident by the present results, as the impact of RBC storage on alloimmunization outcomes was largely preserved even when HOD and KEL were present on the same RBC.…”
Section: Resultssupporting
confidence: 61%
“…RBCs were collected from HOD mice into acid citrate dextrose (ACD) and washed 3 times in 1 × phosphate-buffered saline (PBS). B6 mice were transfused with 50 μL of packed RBCs diluted in PBS to 300 μL total volume via lateral tail vein injection [ 60 , 68 , 77 , 78 , 81 , 83 , 84 , 85 , 86 ].…”
Section: Methodsmentioning
confidence: 99%
“…Even if alloantigen matching efforts or attempts to identify and target pathways to actively inhibit alloantibody formation are successful, [27][28][29][30][31][32][33] these approaches unfortunately do not mitigate the risk of alloantibodynegative DHTRs. 34 Furthermore, in the absence of a positive antibody screen (which can frequently be negative for anamnestic antibodies prone to evanescence), prior alloimmunization events in patients with SCD may be missed and possibly result in the transfusion of inappropriate blood products that increase the risk of developing a DHTR.…”
Section: Limitations Of Antigen Matchingmentioning
confidence: 99%